Manifestations and prognosis of gastrointestinal and liver involvement in patients with COVID-19: a systematic review and meta-analysis - Mao, Ren (Lancet Gastroenterol Hepatol, 2020)
BACKGROUND: The prevalence and prognosis of digestive system involvement, including gastrointestinal symptoms and liver injury, in patients with COVID-19 remains largely unknown. We aimed to quantify the effects of COVID-19 on the digestive system. METHODS: In this systematic review and meta-analysis, we systematically searched PubMed, Embase, and Web of Science for studies published between Jan 1, 2020, and April 4, 2020. The websites of WHO, CDC, and major journals were also searched. We included studies that reported the epidemiological and clinical features of COVID-19 and the prevalence of gastrointestinal findings in infected patients, and excluded preprints, duplicate publications, reviews, editorials, single case reports, studies pertaining to other coronavirus-related illnesses, and small case series (<10 cases). Extracted data included author; date; study design; country; patient demographics; number of participants in severe and non-severe disease groups; prevalence of clinical gastrointestinal symptoms such as vomiting, nausea, diarrhoea, loss of appetite, abdominal pain, and belching; and digestive system comorbidities including liver disease and gastrointestinal diseases. Raw data from studies were pooled to determine effect estimates. FINDINGS: We analysed findings from 35 studies, including 6686 patients with COVID-19, that met inclusion criteria. 29 studies (n=6064) reported gastrointestinal symptoms in patients with COVID-19 at diagnosis, and the pooled prevalence of digestive system comorbidities was 4% (95% CI 2–5; range 0–15; I(2)=74%). The pooled prevalence of digestive symptoms was 15% (10–21; range: 2–57; I(2)=96%) with nausea or vomiting, diarrhoea, and loss of appetite being the three most common symptoms. The pooled prevalence of abnormal liver functions (12 studies, n=1267) was 19% (9–32; range 1–53; I(2)=96%). Subgroup analysis showed patients with severe COVID-19 had higher rates of abdominal pain (odds ratio [OR] 7·10 [95% CI 1·93–26·07]; p=0·003; I(2)=0%) and abnormal liver function including increased ALT (1·89 [1·30–2·76]; p=0·0009; I(2)=10%) and increased AST (3·08 [2·14–4·42]; p<0·00001; I(2)=0%) compared with those with non-severe disease. Patients in Hubei province, where the initial COVID-19 outbreak occurred, were more likely to present with abnormal liver functions (p<0·0001) compared with those outside of Hubei. Paediatric patients with COVID-19 had a similar prevalence of gastrointestinal symptoms to those of adult patients. 10% (95% CI 4–19; range 3–23; I(2)=97%) of patients presented with gastrointestinal symptoms alone without respiratory features. Patients who presented with gastrointestinal system involvement had delayed diagnosis (standardised mean difference 2·85 [95% CI 0·22–5·48]; p=0·030; I(2)=73%). Patients with gastrointestinal involvement tended to have a poorer disease course (eg, acute respiratory distress syndrome OR 2·96 [95% CI 1·17–7·48]; p=0·02; I(2)=0%). INTERPRETATION: Our study showed that digestive symptoms and liver injury are not uncommon in patients with COVID-19. Increased attention should be paid to the care of this unique group of patients. FUNDING: None.